2018
DOI: 10.1055/a-0577-3500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endocuff-assisted colonoscopy on adenoma detection rate: meta-analysis of randomized controlled trials

Abstract: With moderate-quality evidence, this study showed an improvement in ADR with EAC without major adverse events, especially for operators with low-to-moderate ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 32 publications
5
63
2
2
Order By: Relevance
“…Williet et al . reported in their meta‐analysis that the ADR was significantly higher in the EAC group than in the SC group, especially for operators with low‐to‐moderate ADRs (< 35%); however, no benefit was achieved for operators with high ADRs (> 45%) . In our study, the ADR in both the EAC and TAC groups was > 50%.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Williet et al . reported in their meta‐analysis that the ADR was significantly higher in the EAC group than in the SC group, especially for operators with low‐to‐moderate ADRs (< 35%); however, no benefit was achieved for operators with high ADRs (> 45%) . In our study, the ADR in both the EAC and TAC groups was > 50%.…”
Section: Discussioncontrasting
confidence: 49%
“…A meta‐analysis of EAC versus SC including four randomized controlled trials, four retrospective cohort studies, and one prospective observational study showed that the ADR was significantly higher in the EAC group than in the SC group . Another recent meta‐analysis of EAC versus SC including 12 randomized controlled trials showed that the ADR and polyp detection rate were significantly higher in the EAC group than in the SC group, and the MAP tended to be higher with EAC . In this study, it was assumed that the ADR in the EAC group may be superior to that in the TAC group; however, the ADR and MAP in the EAC group were not superior to those in the TAC group.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Three meta‐analyses have been performed to confirm the effect of EndoCuff . Fewer studies were included in the early meta‐analysis, and most of these articles were of low quality.…”
Section: Introductionmentioning
confidence: 99%